Doktrin Gereja - Sofiya Cristine; Susilawati; Julia; Sarmauli (CV Edujavare Publishing, 2025)
The Doctrine of the Church is an integral part of Christian theology that defines the identity, function, and mission of the Church in the world. This document systematically discusses the biblical understanding of the Church, its essential attributes—holiness, catholicity, apostolicity, and unity—as well as its role within the community of believers and the broader society. It also highlights the importance of sacraments, spiritual leadership, and the Church’s relationship with the Kingdom of God. Through a theological and exegetical approach, this study aims to provide a deeper understanding of the meaning and purpose of the Church as the body of Christ on earth.